Reasons and Determinants for Perceiving Unmet Needs for Mental Health in Primary Care in Quebec. (June 2015) - Dezetter, Anne; Duhoux, Arnaud; Menear, Matthew; Roberge, Pasquale; Chartrand, Elise; Fournier, Louise
Objective: To evaluate the mental health care needs perceived as unmet by adults in Quebec who had experienced depressive and (or) anxious symptomatology (DAS) in the previous 2 years and who used primary care services, and to identify the reasons associated with different types of unmet needs for care (UNCs) and the determinants of reporting UNCs. Method: Longitudinal data from the Dialogue Project were used. The sample consisted of 1288 adults who presented a common mental disorder and who consulted a general practitioner. The Hospital Anxiety and Depression Scale was used to measure DAS, and the Perceived Need for Care Questionnaire facilitated the assessment of the different types of UNCs and their motives. Results: About 40% of the participants perceived UNCs. Psychotherapy, help to improve ability to work, as well as general information on mental health and services were the most mentioned UNCs. The main reasons associated with reporting UNCs for psychotherapy and psychosocial interventions are "couldn't afford to pay" and "didn't know how or where to get help, " respectively. The factors associated with mentioning UNCs (compared with met needs) are to present a high DAS or a DAS that increased during the past 12 months, to perceive oneself as poor or to not have private health insurance. Conclusions: To reduce the UNCs and, further, to reduce DAS, it is necessary to improve the availability and affordability of psychotherapy and psychosocial intervention services, and to inform users on the types of services available and how to access them.